Banco Ativo de Germoplasma de Minas Gerais (Coffea spp.): aptidão para a produção de Cafés Especiais - Fassio, Larissa de Oliveira (2017)
One of the main instruments that the current Brazilian coffee has to stay on the market, is the quality. As a result of the growing demand for high quality coffees, the interest in planting cultivars of great potential for specialty coffee production has increased significantly in recent years. Hence, initiatives of study quality of different genotypes yield important information about the future of specialty coffee production in Brazil. Therefore, this work aims to evaluate the accesses to Active Germplasm Collection of Minas Gerais as: i) the potential of quality of access in function of two consecutive harvests and characterize the sensory profile of the same; ii) the influence of wet and dry processing in quality and sensory profile of the accesses; iii) to find possible chemical markers to discriminate genealogic groups of Coffea arabica processed by dry method using the partial least-squares discriminant analysis (PLS-DA); iv) to evaluate the discrimination of access processed by pulping through a ranking model PLS-DA. The experiment was conducted at the Active Germplasm Collection of Minas Gerais (BAG) located at Fazenda Experimental da Epamig in Patrocínio, in the Cerrado region of Minas Gerais, in which were evaluated 56 accesses of C. arabica L., deployed in the field in random blocks with two replications and ten plants per plot. The ripe fruits of each plot were collected on crop 2015/2016 and processed by the wet method (fully washed) and dry (natural), dried under the same condition on screenhouse bottom sieves until water content of 11% (wu). The sensory analysis was performed by trained tasters in accordance with the protocols of the SCAA and the chemical analyses were developed by chromatographic and physicochemical methods. For the interpretation of the data it was used chemometric analysis PCA and PLS-DA, and to the characterization of the sensorial nuances it was used the method of Content Analysis. The results of this study demonstrate that the Active Germplasm Collection of Minas Gerais represents an important collection of genotypes with high potential for quality of drink that can be used in breeding programs aiming the production of plant varieties to the market of specialty coffees. The year of harvesting and the processing type adopted influenced in quality and sensory characteristics of some accesses. The classification of genealogic groups from the Active Germplasm Collection of Minas Gerais through the chemical approach using PLS-DA has identified chemical markers for discriminating genotypes by both wet and dry processing, and which ones have a higher influence on analysis response. This study also showed that the model PLS-DA is a good tool to discriminate between accesses of C. arabica, however for cultivars with different genetic background, the classification is not entirely satisfactory, being necessary improvement in the model to sort these cultivars.